Reversible Reaction of Cobalt(II) Tetrasulfophthalocyanine with Molecular Oxygen - J. Vepřek-Šiška; E. Schwertnerová; D.M. Wagnerová (CHIMIA)
Absorption spectra of solutions of Co(II), Fe(III) and Mn III) tetrasulfophthalocyanines have been studied under aerobic and anaerobic conditions. CoTSP reacts reversibly with molecular oxygen forming a stable oxygen adduct. The oxygen adduct with FeTSP is stable only in neutral solution and its formation is not fully reversible. No reaction of MnTSP with oxygen has been found.